Bone marrow mesenchymal stem cells overexpressing stromal cell- derived factor 1 aid in bone formation in osteoporotic mice - Yanghao Wang; Ya Xiao; XinYu Yang; Fei He; Jun Hu; Guang Yang; Weizhou Wang (BMC Musculoskeletal Disorders)
Abstract Background Osteoporosis is characterized by low systemic bone mineral content and destruction of bone microarchitecture. Promoting bone regeneration and reversing its loss by infusion of exogenous bone marrow mesenchymal stem cells (BMSCs) is a potentially effective treatment for osteoporosis. However, their limited migration to target organs reduces the therapeutic effect of the cells. Stromal cell-derived factor 1 (SDF1) is a chemokine that induces targeted cell migration through the SDF1/CXCR4 (C-X-C chemokine receptor 4) axis and can induce migration of exogenous mesenchymal stem cells to sites of high SDF1 concentration. There are no studies on BMSCs overexpressing SDF1 (SDF1-BMSCs) in osteoporotic mice in vivo. We aimed to investigate if the increased SDF1 concentration facilitated cell migration to the bone. Methods We used lentivirus to construct BMSCs overexpressing SDF1 or knocking down CXCR4. We verified the proliferation ability of the cells in vitro using Cell Counting Kit-8 (CCK8) and 5-Bromodeoxyuridinc (BrdU), the migration ability of the cells using Transwell, and the osteogenic and lipogenic ability of the cells using osteogenic and lipogenic induction solutions. In in vivo experiments, we induced osteoporosis in 72 female mice by ovariectomy and injected different groups of cells via the tail vein. Femoral tissue samples were collected for a fixed time, and the osteogenic and homing abilities of the cells were verified by MicroCT and tissue section staining. Results We successfully demonstrated that high expression of SDF1 promoted cell proliferation and migration in vitro, without affecting their cell differentiation ability. In an ovariectomized mouse model, SDF1-BMSCs were more likely to be home to the femur than the BMSCs, had a better pro-osteogenic ability, and had higher expression of Wnt-1. Blocking the SDF1/CXCR4 axis reduced the homing of exogenous mesenchymal stem cells (MSCs) to the femur and their osteogenic capacity. Conclusions SDF1-BMSCs can further promote bone formation by increasing the number of cells homing to the femur in osteoporotic mice. Our study shows that stem cells can promote their proliferation and home to the femur via the SDF1/CXCR4 axis and further help bone formation via Wnt-1 signaling.